2020
DOI: 10.2196/19474
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Enablers to Using a Patient-Facing Electronic Questionnaire: A Qualitative Theoretical Domains Framework Analysis

Abstract: Background Electronic patient questionnaires are becoming ubiquitous in health care. To address care gaps that contribute to poor asthma management, we developed the Electronic Asthma Management System, which includes a previsit electronic patient questionnaire linked to a computerized clinical decision support system. Objective This study aims to identify the determinants (barriers and enablers) of patient uptake and completion of a previsit mobile hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…A limitation of electronic questionnaires is the reliance on patients to accurately self-report symptoms and exacerbations, which introduces recall and other biases that could impact validity [ 21 , 22 ]. Another challenge of implementation is the limited uptake of questionnaires by clinicians and patients who are provided electronic questionnaires [ 23 , 24 ]. Overall, questionnaires have been shown to be effective for improving the diagnosis of asthma by gaining additional insight into patient symptoms and history, however difficulties related to accuracy and uptake of these electronic questionnaires remain.…”
Section: Resultsmentioning
confidence: 99%
“…A limitation of electronic questionnaires is the reliance on patients to accurately self-report symptoms and exacerbations, which introduces recall and other biases that could impact validity [ 21 , 22 ]. Another challenge of implementation is the limited uptake of questionnaires by clinicians and patients who are provided electronic questionnaires [ 23 , 24 ]. Overall, questionnaires have been shown to be effective for improving the diagnosis of asthma by gaining additional insight into patient symptoms and history, however difficulties related to accuracy and uptake of these electronic questionnaires remain.…”
Section: Resultsmentioning
confidence: 99%
“…Our study highlights several potential sources of this apprehension, including reluctance to changing established self-monitoring routines; concern that mHealth may be used to reduce or replace in-person care; fear, anxiety, and lack of confidence around mHealth use; and reluctance to accept mHealth that is not endorsed or recommended by trusted health care sources. Other than concerns about mHealth replacing in-person care and anxiety about being required to use mHealth [ 33 , 42 ], these findings are novel compared to qualitative studies of younger adults with airway disease, where apprehensions around mHealth use have focused more around privacy or security and technological reliability [ 39 , 41 , 43 ]. Strategies to address these apprehensions specific to older adults are proposed in Table 2 , as detailed above.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of patients failed to complete end of trial questionnaires despite multiple reminders, though this is perhaps unsurprising given the use of remote electronic questionnaires. An assessment of patients with asthma found that key enablers to completing an electronic health questionnaire included ease and convenience of completion, patient-perceived priority and usefulness of the questionnaire and its findings [ 37 ].…”
Section: Discussionmentioning
confidence: 99%